Algoritmo para diagnóstico de retenção urinária pós-operatória por ultrassonografia à beira leito: estudo metodológico. - Farias, Carlos Alexandre dos Santos; Souza, Priscilla Alfradique de; Ramalho Neto, José Melquíades; Bitencourt, Graziele Ribeiro (Acta Paulista de Enfermagem, 2025)
The article focuses on the development and validation of a clinical algorithm for the nursing diagnosis of urinary retention in adult patients in the immediate postoperative period of hip or knee arthroplasties, using bedside bladder ultrasonography. The study, conducted between May and August 2022, involved 127 specialists from various parts of Brazil, who evaluated the algorithm using the Content Validity Index (CVI), resulting in an overall validation of 0.842, indicating high agreement. The algorithm, named Bladder Scanning Algorithm for Urinary Retention Assessment using Ultrasonography for Nurses (BladScanNurse), can be implemented in postoperative care units, aiming to improve the identification of urinary retention and decision-making regarding bladder catheterization. The research highlights the importance of using technologies such as ultrasonography to enhance nursing practice and the quality of patient care.